HUBUNGAN PERAN PERAWAT SEBAGAI CARE GIVER DENGAN KELENGKAPAN PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUANGAN RAWAT INAP RSUD BOLAANG MONGONDOW UTARA - Nur Hovifah Sukarno; Silvia D Mayasari Riu; Norman Alfi Talibo (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Documentation plays a role as evidence of accoun tability and a legal basis for nurses in carrying out their duties. If nursing activities are not documented properly, accurately, objectively, and completely, and are not in accordance with nursing care standards, it will be difficult to prove that nursing actions have been carried out correctly. The purpose of this study is to determine and analyze the relationship between the role of nurses as caregivers and the completeness of nursing care documentation in inpatient rooms. This study uses a cross-sectional research design with a quantitative approach and a descriptive-analytic research design. The population in this study was 94, with a sample of 48 respondents. The sampling technique used purposive sampling. Data were collected through questionnaires and observation sheets. Data were analyzed using the Chi-Square statistical test with a p-value of 0.05. The results showed that the role of nurses as caregivers was good with complete documentation in 23 respondents (90.2%), while the role of nurses as caregivers was less good with incomplete documentation in 21 respondents (91.3%). Based on the chi-square test results, the p-value obtained was 0.000.The conclusion of this study is that the role of nurses as caregivers is mostly categorized as good, and the completeness of nursing care documentation is partly categorized as complete, and there is a relationship between the role of nurses as caregivers and the completeness of nursing care documentation. ABSTRAK Dokumentasi berperan sebagai bukti pertanggung jawaban dan dasar hukum bagi perawat dalam melaksanakan tugasnya. Jika kegiatan keperawatan tidak didokumentasikan dengan baik, akurat, obyektif, dan lengkap serta sesuai dengan standar asuhan keperawatan maka sulit untuk membuktikan bahwa tindakan keperawatan telah dilakukan dengan benar. Tujuan penelitian ini adalah untuk mengetahui dan menganalisis adanya hubungan antara peran perawat sebagai care giver dengan kelengkapan pendokumentasian asuhan keperawatan di ruang rawat inap. Metode Penelitian ini menggunakan jenis penelitian cross-sectional dengan pendekatan kuantitatif dan rancangan desain penelitian deskriptif analitik. Populasi dalam penelitian ini sebanyak 94 dengan sampel 48 responden. Teknik pengambilan menggunakan purposive sampling, Data dikumpulkan melalui kuesioner dan lembar observasi. Data dianalisis menggunakan Uji Statistik Chi-Square dengan nila p-value 0,05. Hasil penelitian menunjukan bahwa peran perawat  sebagai care giver  baik dengan kelengkapan pendokumentasian yang baik berjumlah 23 responden (90,2%) sedangkan peran perawat sebagai care giver kurang baik dengan kelengkapan pendokumentasian yng kurang baik berjumlah 21 responden (91,3%). Berdasarkan hasil uji chi-square didapatkan hasil nilai p value = 0,000. Kesimpulan pada penelitian ini peran perawat sebagai care giver sebagian besar dikategorikan baik dan kelengkapan pendokumentasian asuhan keperawatan sebagian dikategorikan lengkap, serta terdapat hubungan antar peran perawat sebagai care giver dengan kelengkapan pendokumentasian asuhan keperawatan.